Makna Interaksi Kasih Sayang pada Komunikasi Keluarga Lesbian, Gay, Biseksual, dan Transgender: Studi Fenomenologi pada Individu Pelaku Lesbian, Gay, Biseksual, dan Transgender - Qudria, Syavira; Tayo, Yanti; Oktariani, Fardiah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The lesbian, gay, bisesksual, and transgender phenomena are a social reality that has existed in Indonesia for decades. While this phenomenon develops over time, some indonesians view lesbian, gay, bisexual and transgender as aberrant sexual behavior. In Indonesia, LGBT life often closes out of fear of social stigma and discrimination by people around it. Some cases of prosecution against the LGBT have taken away their rights, and have created a controversial situation. And communication between LGBT with society and families is difficult. The study USES qualitative methods with a string of phenomena approaches, with a view to finding meaning, motive, and communication experiences for LGBT practitioners, the study USES a string theory called string theory alferd schutz. As for the informant in this study, there are lesbian, gay, bisexual, and transgender individuals who number five. In order to get the meaning, motive, and experience of LGBT researchers, researchers must do extensive research in order for the informant to provide the truth. Research shows that informants have a mixed sense of family love, which is support, acceptance, and denial. As for the motive that drives the informer to be LGBT, which is the instinctive feelings, the inroles and affections of the parents, the association, the trauma of the past, and the overwhelming admiration.